Atlas of implantable therapies for pain management - Deer, Timothy; (editor & added author).; SpringerLink (Online service). (New York London Springer, 2010)
As of Implantable Therapies for Pain Management This atlas is an essential guide for all implanters, from beginners to the most advanced practitioners. The process of implanting and managing spinal cord stimulators, peripheral nerve stimulators, and intrathecal pumps, from the beginning through long-term management, is thoroughly discussed, as are the prevention and management of complications. Extensive photographs and detailed instructions make each segment a great learning event. The Atlas of Implantable Therapies for Pain Management is a ?must-have? resource for any physician wishing to improve his or her skills in interventional pain treatment. ABOUT THE AUTHOR TIMOTHY DEER, MD, is President and Chief Executive Officer of the Center for Pain Relief in Charleston, West Virginia and Clinical Professor of Anesthesiology, West Virginia University School of Medicine, Morgantown. Dr. Deer is the immediate past Chair of the Committee on Pain Medicine for the American Society of Anesthesiologists; a member of the Boards of Directors of the American Academy of Pain Medicine and the American Society of Interventional Pain Physicians; and a member of the Board of Directors and The Executive Board of the International Neuromodulation Society. He is also Chairman of the Scientific Review Committee of the American Academy of Pain Medicine, Chairman of the Scientific Oversight Committee for Pain Medicine of the American Society of Anesthesiologists, and the current President of The West Virginia Society of Interventional Pain Physicians. He lectures widely on the topic of implantable therapies in pain management and is one of the most respected proponents of these therapies worldwide.
Part 1. Neurostimulation: Spinal Cord Stimulation -- History of Neurostimulation -- Spinal Cord Stimulation: Indications and Selection -- Needle Placement for Percutaneous Spinal Cord Stimulation of the Back and Legs -- Physician Guided Lead Placement: Making the Lead go to the Target -- Anchoring Percutaneous Leads During Permanent Device Placement -- Tunneling Spinal Cord Stimulation Systems -- Pocketing Techniques -- Complications of Spinal Cord Stimulation -- Programming Spinal Cord Stimulation Systems -- Stimulation of the Spinal Cord by the Placement of Surgical Based Paddle Leads -- Part 2. Neurostimulation: Peripheral Nerve and Peripheral Nerve Field Stimulation -- Stimulation of the Peripheral Nervous System -- Stimulation of the Nervous System to Treat Neuropathic Pain of the Foot -- EMG/SSEP Monitoring During Thoracolumbar Spinal Cord Stimulation -- Sacral Nerve Root Stimulation for the Treatment of Pelvic and Rectal Pain -- EMG/SSEP Monitoring During Sacral Neuromodulation -- Selective Nerve Root Stimulation: Facilitating the Cephalocaudal Retrograde Method of Electrode Insertion --Part 3. Neurostimulation: Stimulation of the Cranium and Head -- Stimulation of the Deep Brain for the Treatment of Chronic Pain -- Stimulation of the Motor Cortex to Treat Chronic Pain -- Stimulation of the Peripheral Nervous System: Occipital Techniques for the Treatment of Occipital Neuritis and Transformed Migraine -- Part 4. Drug Delivery -- History of Intrathecal Drug Delivery -- Selection and Indications for Intrathecal Pump Placement -- Placement of Intrathecal Needle and Catheter for Chronic Infusion -- Securing and Anchoring Permanent Intrathecal Catheters -- Tunneling Permanent Intrathecal Catheters -- Pocketing for Intrathecal Drug Delivery Systems -- Drug Selection for Intrathecal Drug -- Delivery -- Intrathecal Pump Refills -- Complications of Intrathecal Drug Delivery.
Electronic reproduction.
Keywords: Pain -- Treatment -- Atlases; Implants, Artificial -- Atlases; Electric stimulation therapy -- methods -- Atlases; Pain -- Prevention & control -- Atlases; Drug implants -- Atlases; Implantable neurostimulators -- Atlases; Infusion pumps, Implantable -- Atlases; Electronic books